Chronic Chagas disease: Can prophylaxis and therapeutic vaccines crack this "hard nut"? - Bontempi, Iván (2016)
Although, none of the therapeutic vaccines assessed so far have reached sterilizing immunity, the results obtained in terms of disease control indicate that immune intervention might be used for therapeutic purposes.